A national, multicenter, retrospective study evaluating retention rate and efficacy of tocilizumab treatment in patients with active rheumatoid arthritis who had an inadequate response to csDMARDs and/or TNF inhibitors - İNANÇ, GÜZİDE NEVSUN (My University, 2023)
Background/aim: To describe the disease activity and retention rate in rheumatoid arthritis (RA) patients with inadequate response (IR) to conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) and/or tumor necrosis factor inhibitors (TNFis) who were prescribed tocilizumab (TCZ) as first-line or second-line biologic treatment in real-world setting. Materials and methods: Data gathered from patients’ files was used in a multicenter and retrospective context. Retention rates and the Disease Activity Score in 28 joints with CRP (DAS28-CRP) were evaluated at time points. The relationship of drug efficacy with factors such as smoking, obesity, and previous use of TNFis was also examined. Results: One hundred and twenty-four patients with a median (IQR) RA duration of 3.7 (7.4) years were included. Mean (SD) age was 52.9 (12.9) and 75% of the patients were female. TCZ retention rates in the 6th and 12th months were 94.1% and 86.6%, respectively. In all patients, DAS28-CRP level decreased significantly from baseline to Months 3 and 6. There was an increase in patients with remission and/or low disease activity and a decrease in patients with high disease activity at Month 3 and Month 6 (p < 0.001 for both). Disease activity was similar between subgroups based on body mass index, smoking status, and previous use of TNFis at any time point. Regres-sion analysis showed that absence of concomitant corticosteroid treatment independently was associated with remission/LDA achieve-ment at Month 6 [OR = 0.31, 95% CI (0.14– 0.72), p = 0.006], and Month 12 [OR = 0.35, 95% CI (0.13–0.94), p = 0.037]. Overall, 25 mild adverse events were reported. Conclusion: TCZ was found to be effective and safe in RA patients with IR to csDMARDs and/or TNFis. The drug retention rate was considered satisfactory with more than half of the patients continuing TCZ treatment at Month 12.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; anti-interleukin-6; Rheumatoid arthritis; tocilizumab